2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29982
|View full text |Cite
|
Sign up to set email alerts
|

Board 20: Work in Progress: Biomedical Prototype Design in Collaborative Teams to Increase Students' Comprehension and Engagement

Abstract: is a graduate student at the University of New Mexico in Biomedical Engineering. She has previous experience as a secondary science teacher at the high school level. Based on her observations as both a teacher and a student, Kiersten believes that the most effective way to teach is through creative lesson plans paired with collaborative problem-based learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We brought in faculty from other universities and departments, not only to learn from them, but to learn together, as we found that the most engaging and useful workshops were those that opened up discussions of concerns and shifted into generative discussions of ways faculty could resolve their concerns and try out new approaches [34]. This approach supported faculty beyond the guiding team to engage in inquiry about their teaching and its effect on learning [35]. In addition, early in the project, through external evaluation, we discovered a covert value: all of our faculty expressed that they valued teaching, but many assumed their peers did not likewise value it.…”
Section: Embed a Community Of Practice In Existing Structures And Normsmentioning
confidence: 99%
“…We brought in faculty from other universities and departments, not only to learn from them, but to learn together, as we found that the most engaging and useful workshops were those that opened up discussions of concerns and shifted into generative discussions of ways faculty could resolve their concerns and try out new approaches [34]. This approach supported faculty beyond the guiding team to engage in inquiry about their teaching and its effect on learning [35]. In addition, early in the project, through external evaluation, we discovered a covert value: all of our faculty expressed that they valued teaching, but many assumed their peers did not likewise value it.…”
Section: Embed a Community Of Practice In Existing Structures And Normsmentioning
confidence: 99%